Business in Asia Pacific - Kahal, Sonia El (Oxford University Press, 2001)
This book synthesizes an account of the Asia Pacific business environment with an analysis of management styles and decision-making techniques. The writing style is clear and easy to read throughout, and the author employs a variety of teaching and learning aids including case material, learning objectives, and chapter exercises which will help the student to take a more active approach to studying this popular topic on business and management courses